A aprendizagem da docência em matemática a partir da elaboração de uma situação desencadeadora da aprendizagem - Ferreira, Cezar Augusto (2019)
This work was developed from the care with the appropriation of knowledge about the learning of teachers of future mathematics teachers. The question that guided this research was “what are the contributions of the process of elaborating a Learning Trigger Situation to the teaching learning of teachers who participate in the math club?” The main objective was to investigate the contributions of the process of elaborating a Triggering Learning Situation for the teaching learning of teachers who participate in the math club. The theoretical basis was based on the assumptions of the Historical-Cultural Theory, the Activity Theory and the theoretical-methodological elements of the Teaching Guiding Activity. This research is linked to the research project - Mathematics Club / CluMat of the State University of Goiás Campus Quirinópolis. The project involves, elaborates and develops teaching activities that prioritize mathematical contents taught in both Elementary and Secondary Education. From this perspective, students of the Mathematics undergraduate course participating in CluMat - subjects of this research - elaborated a study task about the concept of numbers, which was developed in classes of 3rd, 4th, 5th and 6th grades of elementary school. The methodological approach was the formative experiment and to obtain the data a field diary of the researcher and audio and video recordings of 27 meetings, as well as photographic records. The data organization was based on three units of analysis: 1 - The organization of teaching in motion: The planning of the actions of the study task; 2 - The importance of collectivity as a preponderant element for the development of SDA and, consequently, of teaching learning and 3 - Learning of teaching in mathematics from the elaboration and development of SDA. For the analysis process were relevant the units of analysis of Vygotsky (1993), the episodes and scenes of Moura (2004) and flashes of Silva (2014). Regarding the results, there was evidence that there was a change of meaning in the actions that make up the pedagogical activity of the subjects, since from the development of these new meanings the future teachers gave signs of appropriation of the necessary knowledge for the teaching practice, establishing the learning movement of teaching in Mathematics from the elaboration of a triggering learning situation in the context of the Mathematics Club.